Formulation, Evaluation and Release Mechanism of Ketoconazole Microsponge by Liquid-Liquid Suspension Polymerization Method - S. Parimalakrishnan (Journal of Global Pharma Technology, 2019)
The aim of the present study is to formulate a microsponge based release system contains ketoconazole for controlled release of drugs for an effective fungal treatment. Compatibility study involving drug and polymer mixture done by FTIR and was initiate to be compatible. Ketoconazole loaded microsponges were prepared by liquid-liquid suspension polymerization method using ethyl cellulose and hydroxypropyl methylcellulose as polymers with different drug polymer ratios. Later, formulated microsponges were characterized. The particle size was measured by SEM, entrapment efficiency by assay and in vitro drug release profile by dissolution. The effect of preparation variables such as a drug to polymer ratio and stirring speed on the physical characteristics of microsponges is examined. The formulated microsponges were spherical and porous, with a mean particle size of 100μm at 400 magnifications. 87.6% of drug was entrapped in the system and 89.40% of drug was released at 12th hour from FII. From the above findings, we conclude that microsponges were prepared successfully and evaluated. The evaluation report shows that the sizes of the particle are within the range and controlled release of drug was achieved. This indicates that polymer choosen for the study is appropriate. The mathematical kinetic modeling shows that FII formulation undergoes zero order kinetic and follows Higuchi model, which follows diffusion mechanism in the release of drugs.Keywords: Ketoconazole, Microsponges, Ethyl cellulose, Hydroxypropyl methylcellulose, Liquid-Liquid suspension polymerization.